Hotel property information portal using GIS (Geographic Information System) scope of research: Shah Alam Selangor / Nur Adlina Md Radzi - Md Radzi, Nur Adlina (2010)
The main purpose of this research is to provide a hotel property information portal system for public or tourist searching. Based- hotel property information portal system is a simple guide and has been designed to assist the public or tourist and specially for Tourism Selangor to find the location and information of hotel. The creation of this GIS-Based Hotel Property Information Portal System is predominantly to create something simple nevertheless it will be highly beneficial for the society especially in marketing of hotel. This research aims are: 1) to provide the location and information of hotel at Shah Alam area.2) To provide the location of interested place at Shah Alam. The development of the spatial database is using online GIS by apply programming interface using Google Map API platform and JavaScript.. The research methodology for this research consists of four (4) stages. First stage is identifying the research problem, objectives and determination of the case study. Second stage is finding the literature review for this research from various sources. Third stage is creation of spatial database according to the selected case study based on the information given by the hotel marketing advertise and information. To create web services in programming interface the procedures are begin with web design, deriving Google Map API code, preparing a map (extent), identifying coordinates, adding point location and finally adding attributes information. The hotel property information portal is ready to be used. This research might be useful as an marketing tools to the Tourism Selangor, and UiTM portal especially during convocation and registration. The user of this system easily can find the location and information hotel in this portal as a final result display.